2004
DOI: 10.1039/b316651a
|View full text |Cite
|
Sign up to set email alerts
|

Stable π-dimer of a tetrathiafulvalene cation radical encapsulated in the cavity of cucurbit[8]uril

Abstract: The first stable pi-dimer of a tetrathiafulvalene (TTF) cation radical encapsulated in the cavity of cucurbit[8]uril has been isolated at room temperature and fully characterized; it shows absorption bands at 400, 540 and 760 nm, characteristic of the TTF cation radical dimer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
125
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(140 citation statements)
references
References 35 publications
8
125
0
6
Order By: Relevance
“…In the solid state, neutral TTFs weakly stack to form dimers or columnar structures through S£S and ³³ interactions (A), whereas neutral TTFs easily dissociate in solution. 13 In contrast, ³-extended TTF derivatives and TTFs having amphiphilic properties self-associate even in solution, resulting in the formation of nanostructures. 57 Furthermore, stronger molecular interactions occur in mixed valence (MV) states with strong charge resonance (CR) (B).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the solid state, neutral TTFs weakly stack to form dimers or columnar structures through S£S and ³³ interactions (A), whereas neutral TTFs easily dissociate in solution. 13 In contrast, ³-extended TTF derivatives and TTFs having amphiphilic properties self-associate even in solution, resulting in the formation of nanostructures. 57 Furthermore, stronger molecular interactions occur in mixed valence (MV) states with strong charge resonance (CR) (B).…”
mentioning
confidence: 99%
“…3,12 However, there are some ambiguities in the reported MV and ³-dimer states of TTFs in solution because the formation of those states are discussed on the basis of various spectroscopic data. 12c, 13 In order to obtain accurate spectroscopic information about the MV and ³-dimer states of TTFs, we prepared 1,8-bis(tetrathiafulvalenyl)naphthalenes 1a1c (Chart 1) as a model system. Since two TTF units are attached at the 1,8-positions of the naphthalene ring in 1a1c, the face-to-face interactions between two TTFs can be determined very easily.…”
mentioning
confidence: 99%
“…36−39 Further, [n.n]-quinquethiophenophanes and α,ω-bis(quinquethienyl)alkanes have also been studied as π-dimer models. 40,41 More relevant to this study, some intriguing recent reports have also shown that vinyl-linked tritylthiafullvene radicals can form intermolecular dimers 42 that can switch spin with temperature changes in organic solution 43 or via reversible encapsulation in the cavity of a macrocyclic host to stabilize π-dimer form, 44 but a more general strategy for designing organic molecules with stimuliswitchable spin states would be desirable, particularly if this switching is achievable in water to allow for biological applications.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…31,32 Furthermore, the oxidized form of derivative 3 exhibited a strong absorption band with a maximum at 760 nm. According to the literature, 33 the UV-vis absorption at around 760 nm is assigned to a dimer structure of the mono-oxidized TTF moieties. Therefore, the oxidation of derivative 3 caused the formation of a stacked structure of the TTF moieties in solution.…”
Section: Chemical Oxidation Of Ttf Moietiesmentioning
confidence: 99%